2002
DOI: 10.1097/00003246-200204000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Very early extubation in children after cardiac surgery*

Abstract: Successful early extubation of even young children is possible and easily accomplished in most children undergoing cardiopulmonary bypass, even with complex procedures, but advantages of extubation in the operating room vs. immediate ICU extubation remain unclear. Transient mild-to-moderate mixed acidosis is common and requires no treatment. Full implementation requires acceptance by surgical and ICU staffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
1
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 11 publications
7
56
1
8
Order By: Relevance
“…Early extubation could result with mild respiratory acidosis, but contrary to results of the Kloth and Baum study (18), arterial blood gases analyses were in referral values during postoperative period.…”
contrasting
confidence: 87%
See 2 more Smart Citations
“…Early extubation could result with mild respiratory acidosis, but contrary to results of the Kloth and Baum study (18), arterial blood gases analyses were in referral values during postoperative period.…”
contrasting
confidence: 87%
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 71%
See 1 more Smart Citation
“…In 1980, Barash and colleagues 1) reported their experiences with early extubation, and more recently, several studies have suggested that extubation can be performed safely in the operating room (OR) for simple and complex surgical cases in all age groups. [2][3][4] However, the success rate of early extubation in children has been variable and dependent on inclusion and exclusion criteria, such as the patient's age, case severity, and procedure complexity. 5,6) An analysis using the Risk Adjustment in Congenital Heart Surgery method (RACHS-1) revealed that success rate of early extubation became more variable in complex, high-risk cases, such as those with pulmonary hypertension, excessive pulmonary blood flow with a degenerative vascular bed, and/or single ventricular physiology.…”
mentioning
confidence: 99%
“…As principais complicações relacionadas ao aparelho respiratório são 22 : -pneumotórax devido à abertura da pleura durante o ato cirúrgico. Deve ser drenado, se é muito extenso ou hipertensivo;…”
Section: Sistema Respiratóriounclassified